Pengaruh Penambahan Glukomanan sebagai Pengenyal Alami terhadap Kualitas Tekwan Ikan Patin" - Razin, Muhammad (Advances In Social Humanities Research, 2024)
The research aimed to study and analyze the influence of adding glucomannan as a natural thickening agent on the physical quality and consumer acceptance of catfish tekwan. The study was conducted at the Food Processing Laboratory of the Department of Culinary Education, Jakarta State University. The research commenced in August 2022 and concluded in December 2023. The methodology employed was experimental. The research samples consisted of catfish tekwan with the addition of glucomannan in proportions of 1%, 2%, and 3%, evaluated by 30 moderately trained panelists assessing various aspects. The statistical hypothesis tests, specifically the Friedman test, revealed that overall, the addition of 1%, 2%, and 3% glucomannan to catfish tekwan did not significantly impact consumer acceptance in terms of color, saltiness, umami taste, catfish aroma, fishy smell, chewiness, stickiness, and surface smoothness. Furthermore, the ANOVA test for physical quality showed that the level of chewiness did not exhibit a significant difference due to the addition of 1%, 2%, or 3% glucomannan in the production of catfish tekwan. The conclusion drawn from this study recommends the use of 3% glucomannan in catfish tekwan for the development of natural thickening agents.